Inherent health oriented design for preventing sick building syndrome during planning stage. (December 2021) - Gao, Xiaoming; Jali, Zakiah Mat; Abdul Aziz, A.R.; Hizaddin, Hanee F.; Buthiyappan, Archina; Jewaratnam, Jegalakshimi; Bello, Mustapha M.
Abstract: Derived from inherent safety concept, inherent health is a new approach that aims to unearth proactive, fundamental, and permanent solutions that could eliminate or significantly reduce health risks at source, thus avoiding adding extensive end-of-pipe protections. To date, however, limited attention has been given to using this new approach to prevent Sick Building Syndrome (SBS), and an assessment tool for quantifying the "sickness" at planning stage is yet to be established. To this end, this work investigated the feasibility of addressing SBS via Inherent Health Oriented Design (IHOD) and developed SBS Contributory Indices (SBSCI) for quantifying the sickness severity. Firstly, the contributory indices were extracted from a well-practiced checklist of SBS determinants. Then, the indices were reconciled using Analytic Hierarchy Process (AHP) and equation-based Bayesian Networks (BN), and finally, the newly developed metric (i.e., SBSCI) was exemplified by a case study. The results show that the sickness level decreased by approximately 82% after IHOD modifications, implying that the modified architectural design can be less sick (inherently healthier) than the baseline design. This work presents a nexus study between the implications of "inherent" solutions and healthy buildings. This cross-cutting study would offer a new perspective on the early inspection and prevention for sick building induced health problems. Highlights: Adapted causal model of Sick Building Syndrome (SBS) symptoms Checklist for preventing SBS symptoms during building planning stage Bayesian Networks (BN) based modeling and simulation Inherent Health Oriented Design (IHOD) modifications for SBS causes Comparison of architectural design alternatives using IHOD concept